Pengembangan Chatbot untuk Informasi Wisata Interaktif di Tangerang Selatan menggunakan Framework Rasa - Ferdian, Aldi Dwi; Anwar, Sariyun Naja (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Tangerang Selatan is a city in Indonesia known for its captivating tourism potential, particularly in the realms of historical, culinary, and cultural attractions. However, tourists often face challenges in obtaining accurate and comprehensive information about the various tourist destinations in Tangerang Selatan. Furthermore, with the rapid advancement of technology, there is an increasing demand for quick and easily accessible information. Therefore, this research focuses on developing a tourism information chatbot using the Rasa framework. The chatbot aims to provide tourists with reliable, interactive, and convenient access to information about the captivating tourism offerings in Tangerang Selatan, thereby enhancing the overall tourist experience and promoting the city's tourism sector.. Keywords: : Tourism information, Chatbot,Framework Rasa